Effects of Cover-Plate Geometry on the Mechanical Behavior of Steel Frame Joints with Middle-Flange and Wide-Flange H-Beams - Osama Zaid Yahya Al-Ansi; Linfeng Lu; Saleem Mohammed Ali Ahmed AL-Saeedi; Bingyou Liu (Buildings)
This study investigates the mechanical behavior of cover-plate reinforced connections in steel frames with I-section columns and middle- or wide-flange H-beams, addressing gaps in current design standards. Finite element analyses validated by experimental data were employed to explore the effects of cover-plate geometry—shape, length, and thickness—on seismic performance. Results demonstrate that cover plates improve load-bearing capacity and ductility by relocating plastic hinges outward from joint regions. Specifically, cover-plate connections increased ductility by 25%, yield moment by 15%, and initial rotational stiffness by 7% compared to non-reinforced connections. The shape of the top cover plate had minimal impact on mechanical behavior. The cover-plate length and thickness significantly influenced seismic ductility and load-bearing capacity. The cover-plate thickness should be at least 0.3 times the beam flange thickness (not less than 6 mm) while ensuring the combined thickness of the cover plate and beam flange does not exceed the column flange thickness. These recommendations address the conservatism of existing standards, balancing material efficiency and seismic performance. Optimal cover-plate lengths of 0.7 to 0.9 times the beam depth were also identified. These findings provide practical guidelines for designing resilient steel frame connections in seismic regions.